Low Computational Burden Adaptive Overcurrent Protection for Active Distribution Networks - B. Grisales-Soto; S. Pérez-Londoño; J. Mora-Flórez (International Transactions on Electrical Energy Systems)
Conventional distribution networks have evolved into active distribution networks due to the high penetration of distributed energy resources. These new networks have several protection issues; some are related to the high fault and load current variations due to the various operating conditions. This situation is faced by adaptive protection development, as proposed in this study, where variations among active distribution network operating conditions are considered to estimate the adaptive pickup current. This is used to estimate the overcurrent relay’s time dial setting, avoiding miscoordination. The proposed protection approach uses fast calculations and local measurements; consequently, a low computational burden is required to update the adaptive relay parameters for each operating condition without using communication infrastructure. The obtained results in the IEEE 34-nodes test feeder demonstrate the advantages of the proposed approach, accomplishing the coordinating time interval for phase and ground faults. These results show a high performance of primary and backup protection at different operating conditions of the proposed test system compared to the performance of the conventional protection approach. The proposed approach’s high performance, low computational burden, and communicationless characteristics make it suitable for immediate real-field implementation.